(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In this novel Desai reveals the problems of women and their privileges. They are well aware of their obligations to their lifestyle. She has a place in Indian culture in general, but she speaks several languages and has a voice of her own that is undeniable and extraordinary in its own specific way. In Anita Desai’s compositions we observe that the inner universe of the female characters is revealed. Continues with the mental examination of the female characters to reveal their inner world. In Markandaya’s vast collection of female characters, ranging from grumpy and battered female workers to Haveli princesses, we look at the plight of Indian women who are disadvantaged due to their gender, society and financial situation. Standard Indian culture, dominated by men, limits women to the incredible distance traveled. Shashi Deshpande is one of thebest contemporary Indian novelist in English language. She is one of those extraordinary creators whose civic saints are sensitive, lively, trained, and with professionally mind set. Her concrete attitude towards a certified dissident view on the status of middle-class Indian women is expressed in her original That Long Silence, which won the Sahitya Akademic Award in 1990. Shashi Deshpande’s statements broaden her passion for reflections on Judith Butler, who impressively communicated that La Libertad de la Mujer affirms the distinction between man and woman.